Favourable outcome of patients with breast cancer brain metastases treated with dual HER2 blockade of trastuzumab and pertuzumab. (April 2021) - Bergen, Elisabeth Sophie; Binter, Amelie; Starzer, Angelika Martina; Heller, Gerwin; Kiesel, Barbara; Tendl-Schulz, Kristina; Bago-Horvath, Zsuzsanna; Furtner, Julia; Leitner, Johannes; Exner, Ruth; Fitzal, Florian; Dieckmann, Karin; et al.
Background: Dual human epidermal growth factor receptor 2 (HER2) blockade with trastuzumab and pertuzumab (TP) is a standard therapy of metastatic and localized HER2-positive breast cancer (BC), but its activity in breast cancer brain metastases (BCBM) is unknown. Methods: Patients with HER2-positive BCBM were identified from the Vienna Brain Metastasis Registry and clinical data including patient characteristics, therapies and overall survival (OS) were obtained. Patients were grouped into 'TP', 'other-HER2-targeted therapy' and 'no-HER2-targeted therapy' according to received first-line systemic therapy after diagnosis of BCBM. Radiological re-assessment of intracranial lesions was performed in patients treated with TP as systemic first-line therapy according to RANO response criteria for brain metastases (BM). Results: A total of 252 HER2-positive BC patients with BM were available for this analysis. Patients treated with TP as systemic first-line therapy after diagnosis of BM had a significantly longer OS compared with treatment with other-HER2-targeted therapy and no-HER2-targeted therapy (44 versus 17 versus 3 months, p < 0.001; log-rank test). Among radiologically re-assessed patients treated with TP as systemic first-line therapy after diagnosis of BM, 5/14 patients (35.7%) had complete intracranial remission (CR), 8/14 patients (57.1%) partial intracranial remission (PR), 1/14 patients (7.1%) stable intracranial disease (SD) and 0/14 patients (0.0%) progressive intracranial disease (PD) as best response resulting in an intracranial objective response rate (iORR) of 92.9% and an intracranial clinical benefit rate (iCBR) of 100.0%. Conclusion: First-line therapy with dual HER2-inhibition of TP after BM diagnosis was associated with the longest median OS times in patients with BCBM.